Seasonal trends in donor heart availability: an analysis of the UNOS database. (28th September 2021) - Kamalia, Mohammed A.; Smith, Nathan J.; Rein, Lisa; Ramamurthi, Adhitya; Miles, Bryan; Joyce, Lyle D.; Mohammed, Asim; Joyce, David L.
Summary: Despite the widespread belief that donor organ availability varies around holidays and seasons, there is little empirical data supporting this long‐held belief. Variations in donor heart availability may be of interest to patients and clinicians. The UNOS/OPTN registry was queried for all heart donations from October 1987 through March 2017. Daily heart donation rates were modeled nationally using Poisson regression including splines for year and day of the year. Seasonality was assessed using a likelihood ratio test for the spine terms for day of the year. The holiday effect was assessed using conditional logistic regression. Seasonal plots suggest a significant, although modest, increase in organ availability during the summer months, except for region 1. The regions with the highest amplitude were region 7 (peak: June 21, amplitude: 16.63%) and region 6 (peak: July 5, amplitude: 11.29%). There was no significant difference in the odds of heart donation when comparing holidays vs. non‐holidays using national data (odds ratio [95% CI]: 1.01 [0.98, 1.03], P  = 0.560) or any regional subsets. There was no observable correlation between donor heart availability and holidays. However, a significant seasonality effect was observed with higher donation rates occurring during warmer months. Abstract : In this systematic review we firstly reviewed the reported studies and discussed the use of EBV‐CTLs in the treatment of refractory PTLD of SOT recipients. We found that EBV‐CTL therapy was reliable and effective.